Acquired zinc deficiency in adults: a case report - Yan CAO; Hequn HUANG; Yantao DING; Ze GUO; Anping ZHANG (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2022)
We report a case of acquired zinc deficiency in an adult patient. A 55-year-old woman presented with periocular and perioral rash for 1 month and blisters on both hands and feet for more than 10 days. Dermatological examination showed that her hair was sparse and normal in color. Red macules, patches and scales were observed around both eyes and mouth. Blisters and bullous blisters were observed on the basis of erythema of both palms and wrists, soles and toes. The herpes wall was thick, the herpes fluid was clear, the Nikolsky's sign was negative, and some of the blisters were ulcerated and scabbed, red erosion surface after ulceration was observed in perianal and sacral tail. Scattered red macules and brown crusts were observed on the abdomen and extremities, but the oral and genital mucosa was not involved. Laboratory tests showed that serum zinc level was 70.05 μmol/L and alkaline phosphatase level was less than 20 U/L. Histopathology of skin lesions showed mild hyperkeratosis and epidermal hyperplasia, intracellular and intercellular edema could be seen, small blister formation was observed locally, and a small amount of lymphocyte infiltration around vessels in the superficial and middle dermis. Acquired zinc deficiency was diagnosed. After treatment with zinc gluconate oral solution for one week, the patient's skin lesions were significantly relieved. No recurrence was found during the 3-month follow-up.